Kinetics of leaching of zinc from sphalerite concentrate with sodium persulphate - Babu M.N.; Sahu K.K.; Pandey B.D.; Mankhand T.R. (My University, 2025)
The present investigation deals with the dissolution kinetics of zinc from its sulphide concentrate in the presence of sodium persulphate (SPS) as an oxidant in sulphuric acid media. Leaching variables such as leaching time, temperature, acid and oxidant concentration, Eh and the particle size of sphalerite concentrate were studied to understand the mechanism of the reaction. The kinetic study with sodium persulphate indicated that the leaching of zinc followed a diffusion controlled model and the rate was governed by the diffusion of lixiviant through a porous sulphur layer as the reaction product. An activation energy of 43 ± 2 kJ/mol was acquired for the dissolution of zinc in the temperature range of 303 to 333 K with SPS. The leach residue characterized with the help of X-ray diffraction (XRD) and scanning electron microscopy (SEM) corroborated the diffusion controlled leaching mechanism. © Canadian Institute of Mining, Metallurgy and Petroleum All rights reserved.